2015
DOI: 10.1002/adfm.201500981
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Layer‐Tunable Graphene: A Combined Kinetic Implantation and Thermal Ejection Approach

Abstract: wileyonlinelibrary.comstructure and extraordinary physical properties. [1][2][3][4] To realize the potential of graphene in nanoelectronic devices, a uniform graphene layer with a well-controlled layer number should be synthesized fi rst because most of the physicochemical properties of graphene are sensitive to its thickness. For example, monolayer graphene has a zero band gap, whereas Bernal-stacked (AB-stacked) bilayer graphene is of signifi cant interest for graphene-based fi eld-effect transistors (FETs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 49 publications
0
31
0
1
Order By: Relevance
“…On the other hand, the production of H 2 can, in turn, balance the dehydrogenation of CH 4 . A previous experiment demonstrated that the growth of single graphene in square centimeter needs only 4 × 10 15 atoms, which are estimated to be 1.5 × 10 −4 mL of CH 4 gas . In our SAPCVD system, even though we introduce 1–16 mL CH 4 , far greater than the monolayer graphene growth needs, we can still obtain a uniform single layer in a broad single‐layer window.…”
Section: Resultsmentioning
confidence: 88%
“…On the other hand, the production of H 2 can, in turn, balance the dehydrogenation of CH 4 . A previous experiment demonstrated that the growth of single graphene in square centimeter needs only 4 × 10 15 atoms, which are estimated to be 1.5 × 10 −4 mL of CH 4 gas . In our SAPCVD system, even though we introduce 1–16 mL CH 4 , far greater than the monolayer graphene growth needs, we can still obtain a uniform single layer in a broad single‐layer window.…”
Section: Resultsmentioning
confidence: 88%
“…Carles et al researched the surface‐enhanced raman scattering (SERS) of Ag NP‐embedded substrates . Recently, some researchers have utilized C ion implantation to fabricate graphene on different substrates . Lee et al fabricated large‐scale graphene on Cu foils by ion implantation and subsequent annealing .…”
Section: Ion Beam Techniques For Materials Synthesis and Morphology Cmentioning
confidence: 99%
“…Also, Dharmaraj et al directly grew few‐layer graphene on a SiO 2 substrate by low‐energy carbon ion implantation . Furthermore, Wang et al reported that the number of graphene layers can be controlled by modulating the implantation dosage . Figure shows the Raman spectra and scanning tunneling microscopy (STM) topographical images of monolayer and bilayer graphene synthesized by ion implantation.…”
Section: Ion Beam Techniques For Materials Synthesis and Morphology Cmentioning
confidence: 99%
“…18,19 Therefore, bilayer graphene has been studied extensively, and has been proved having multiple applications in nanoelectronic devices. 20,21 Moreover, with the advance of experimental techniques, the layer-tunable graphene is coming true in a recent research, 22 which makes the synthesis of bilayer graphene easier in experiment. Thus, in order to investigate the spintronic devices based on bilayer graphene, it is very important to investigate the spin-dependent transport behaviours of zigzag-edged bilayer graphene nanoribbons (ZBGNRs).…”
mentioning
confidence: 99%